2021
DOI: 10.30998/jabe.v7i3.8884
|View full text |Cite
|
Sign up to set email alerts
|

Dana Perimbangan Dan Pembangunan Manusia: Sebuah Bukti Pengujian Dari Pulau Kalimantan

Abstract: Bagi Hasil memiliki pengaruh pada pembangunan manusia di Pulau Kalimantan. Riset ini menemukan bahwa implementasi desentralisasi di Indonesia membuat pemerintah daerah cenderung mengandalkan dana perimbangan untuk membiayai program pembangunan manusia di daerah.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…In line with the research conducted by Maria et al, (2021), the results of the research found that the general allocation fund and the special allocation fund partially had a positive influence on human development on the island of Borneo. Meanwhile, the revenue sharing fund has no effect on human development on the island of Kalimantan.…”
Section: Resultssupporting
confidence: 82%
“…In line with the research conducted by Maria et al, (2021), the results of the research found that the general allocation fund and the special allocation fund partially had a positive influence on human development on the island of Borneo. Meanwhile, the revenue sharing fund has no effect on human development on the island of Kalimantan.…”
Section: Resultssupporting
confidence: 82%
“…In contrast, other regions in the province concerned receive a share to equalize income under the portion stipulated in the law. Profit Sharing Funds aim to reduce disparities in financial capacity between the central and regional governments so that regions can determine their use of Profit-Sharing Funds and the Central Government cannot intervene (Maria et al, 2021). The greater the amount of Profit-Sharing Funds received by a region, the greater the possibility of realizing the hope of improving the quality of life through a longer lifespan, better education levels, and a higher standard of living for the community.…”
Section: š‘„100%mentioning
confidence: 99%